Gambaran Kecemasan Akademik pada Mahasiswa Baru Universitas Negeri Padang berdasarkan Faktor Sosiodemografi - Sari, Indah Purnama; Rusli, Devi (TSAQOFAH, 2025)
This study aims to examine the profile of academic anxiety among first-year students of the 2024 cohort at Universitas Negeri Padang. The research involved 416 new students selected through purposive sampling, with data collected online via Google Forms using a Likert-scale questionnaire. The instrument employed was the Academic Anxiety Scale developed by Ottens (1991). This quantitative study utilized two-way factorial analysis of variance (ANOVA) to determine differences in anxiety levels based on age, gender, academic program, and place of origin. The results indicate that, in general, first-year students at Universitas Negeri Padang fall within the moderate category of academic anxiety. This finding suggests that although most students have not yet exhibited severe anxiety symptoms, they still require academic attention and support to prevent an escalation during the early stages of university transition. The implication is that higher education institutions should develop counseling services, orientation programs, and adaptive learning strategies to help new students manage academic demands in a healthy and productive manner.